KESIAPAN KABUPATEN BANTUL DALAM MITIGASI BENCANA DENGAN MENGGUNAKAN SISTEM EVALUASI DRM CAPABILITY ASSESMENT TOOL - , Ragil Andika Y ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The province of Yogyakarta especially Bantul district has been knownasone of theregions in Indonesia that are vulnerable to various disaster threats. Disaster Risk Assessmentreport of Bantul district 2013 â 2017 mentioned that there are 9 (nine) types of disasters that could potentially occur in Bantul. They are earthquake, tsunami, extreme waves and abration, landslides, extreme weather (strong wind), floods, droughts, forest and land fires, and epidemics disease (Bantul DisasterRisk Assessment, 2013). This problem makes an assessment of the readiness of Bantul district in the current disaster mitigation against potential hazard in the region need to be done. Readiness level of a region in the face of disaster will determine the level of disaster risk in the area. All elements of the agency involved in disaster management issues such BPBD Kabupaten Bantul, local governments in 17(seventeen) districts in Bantul district along with all of the community of Bantul district is the object under studied. The assessment is done by using the Disaster Risk Management program using the Capability Assessment Tool-v1. All assessment criteria and parameters that exist in the program is assigned a value based on the data obtained from the field through direct observation, interviews, questionnaires and documentation studies. The results of the assessment for Bantul preparedness in disaster mitigation is gaining score 47,4 with details BPBD Kabupaten Bantul scored 47,8 local government districts scored 46.8 and community of Bantul district scored 47.5.